The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1574-6968.2004.tb09578.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the murine cecal microbiota as revealed by terminal restriction fragment length polymorphism and 16S rRNA gene clone libraries

Abstract: The maturation of murine cecal microbiota was determined by terminal restriction fragment polymorphism (T-RFLP) and 16S rRNA gene clone libraries. Cecal microbiota in specific pathogen free (SPF) mice aged four to 10 weeks were collected. The cluster of samples in 4-week-old mice was different from those of other ages based on T-RFLP profiles. The majority of clones obtained in this study belonged to the Clostridium coccoides (C. coccoides) group, the Bacteroides group or the Lactobacillus group. Phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…However, the intestinal microbiota in experimental animals is quite different in composition from that in humans (23,31). A recent study revealed the existence of many unidentified microorganisms, including some bacteria specific to the mouse intestine, by molecular techniques (2,17,35). Therefore, data obtained in animal experiments cannot be directly applied to humans.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…However, the intestinal microbiota in experimental animals is quite different in composition from that in humans (23,31). A recent study revealed the existence of many unidentified microorganisms, including some bacteria specific to the mouse intestine, by molecular techniques (2,17,35). Therefore, data obtained in animal experiments cannot be directly applied to humans.…”
mentioning
confidence: 89%
“…DNA extraction and purification were based on the methods described by Clement and Kitts (3), using an Ultra Clean Soil DNA isolation kit (Mo Bio Laboratories, Inc., Solana Beach, CA) with some modification, as described previously (17).…”
Section: Animalsmentioning
confidence: 99%
“…It has been previously suggested that T-RFLP analysis is appropriate for monitoring changes in a given community (28). The use of T-RFLP also revealed that the process of colonization of the cecal mucosa by H. hepaticus was associated with reproducible shifts in the overall structure of the microbial community.…”
Section: Fig 4 Comparison Between T-rflp Analysis and In Silico Termentioning
confidence: 94%
“…Following weaning, the cecal community goes through what appears to be a stage of transition before reaching a period of little temporal variation at about 5 weeks of age, which lasts until at least 8 weeks of age. At 10 weeks, however, there is yet another shift in structure (163). Another study, however, suggests that the period of little temporal variation may range from 6 to 15 weeks of age (17).…”
Section: Gastrointestinal Communitymentioning
confidence: 96%